Wage Floors, Imperfect Performance Measures, and Optimal Job Design - Anja Schöttner; Jenny Kragl (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We analyze the effects of wage floors on optimal job design in a moral-hazard model with asymmetric tasks and imperfect aggregate performance measurement. Due to cost advantages of specialization, assigning the tasks to different agents is efficient. A sufficiently high wage floor, however, induces the principal to dismiss one agent or to even exclude tasks from the production process. Imperfect performance measurement always lowers profit under multitasking, but may increase profit under specialization. We further show that variations in the wage floor and the agents' reservation utility have significantly different effects on welfare and optimal job design.
Keywords: M52; M51; M54; 330